Database for the analysis of the integration of Childhood Malnutrition in Low Greenhouse Gas Emissions Livestock - Pérez Marulanda, Lisset (2024)
This database contains data at the municipal level on socioeconomic variables, variables related to deforestation, conflict, livestock production and child malnutrition for the period 2000-2019